Indonesian EFL Teachers’ Challenges: Integrating ICT in EFL Teaching - Bannus, Dedy Arianto; Emeral, Emeral (The Study Program of English Education of Palangka Raya University, 2025)
The influence of ICT in language teaching has become a new, exciting, and demanding area to explore. Moreover, concerning teachers' role as facilitators, it is necessary to explore how they perceive ICT use in language teaching and to describe the challenges they have been experiencing during its implementation. This qualitative study explored the integration and challenges of using ICT in EFL teaching. The participants of this study were six Indonesian EFL teachers from Central Kalimantan Province, and they were interviewed to gain information. The data from semi-structured interviews were thematically analyzed. The results of this qualitative study indicated that the teachers have integrated technological tools into their teaching activities in terms of web-based and non-web-based learning. Laptops and mobile phones were the most prominent technological tools used by the teachers in the classroom. Those technologies are purposively used in teaching EFL skills and evaluation. However, the implementation is challenging, as the teachers argued that they needed more professional training in dealing with technical issues, limited technological tools, internet network issues, and the digital divide. The outcomes strengthen the comprehension of the implementation of technologies in EFL learning and trigger advanced investigation about educational technology influence in the EFL education realm.